Strategi Pertahanan Ekonomi China di Era Xi Jinping : Integrasi Kepentingan Nasional dan Pengaruh Global - Adinda Tias Salsabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article examines the economic defense reforms implemented by China under Xi Jinping's leadership through a literature review. This research aims to examine the key strategies employed by the Chinese government to strengthen its economic resilience amidst global pressures, such as the trade war with the United States, the COVID-19 pandemic, and escalating geopolitical rivalries. The findings indicate that Xi Jinping prioritizes a dual-circulation strategy, namely strengthening domestic consumption while maintaining connectivity with international markets, as a crucial step in addressing global uncertainty. Furthermore, the Made in China 2025 policy serves as a key pillar for promoting technological independence, reducing dependence on imports, and enhancing the competitiveness of domestic industries in strategic sectors such as information technology, renewable energy, and artificial intelligence. Furthermore, through the Belt and Road Initiative (BRI), China seeks to expand its economic influence globally, open new markets, and transfer excess domestic industrial capacity to partner countries. These reforms are not solely oriented toward economic aspects but are also closely linked to political and national security interests. This strategy demonstrates China's systematic efforts to build economic resilience integrated with geopolitical interests, using the economy as an instrument of both soft and hard power. This study demonstrates that Xi Jinping's economic defense reforms are not merely a short-term response to the global crisis, but rather part of a long-term vision to establish China as a dominant global power. Thus, this study emphasizes the importance of understanding China's economic strategy holistically, as these reforms, in addition to significantly influencing domestic dynamics, also have significant implications for the future global economic and political order.